2016
DOI: 10.1111/eje.12243
|View full text |Cite
|
Sign up to set email alerts
|

Roles and competences for educators of undergraduate dental students: a discussion paper

Abstract: Understanding the roles and competences for educators of undergraduate dental students can help individual educators to improve their personal effectiveness and institutions to tailor staff development programmes appropriate to the needs of their staff. Faculty development contributes to sustained enhancement of undergraduate dental education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 34 publications
1
20
0
7
Order By: Relevance
“…Other student cohorts have also reported that retrieval practices were especially helpful in tests that required the integration of both short‐answer and context‐rich multiple‐choice questions (Bradley et al, ; Rosenkranz et al, ; Augustyniak et al, ; Baig and Mallu, ). It has also been observed that repeated retrieval testing of medical and nursing procedures enhanced motor skill retention over long periods of time in these students (Lambert et al, ; Chuenjitwongsa et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other student cohorts have also reported that retrieval practices were especially helpful in tests that required the integration of both short‐answer and context‐rich multiple‐choice questions (Bradley et al, ; Rosenkranz et al, ; Augustyniak et al, ; Baig and Mallu, ). It has also been observed that repeated retrieval testing of medical and nursing procedures enhanced motor skill retention over long periods of time in these students (Lambert et al, ; Chuenjitwongsa et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
“…An alternative method suggested by Silverman is known as the agenda‐led outcome‐based analysis (ALOBA) approach (Silverman et al, , ). In this method, students initially identify issues that they require help with (de Paiva et al, ), and the discussion is directed toward achieving those goals by encouraging self‐assessment (Rosenman et al, ; Chuenjitwongsa et al, , b) and identification of the skills necessary to achieve these outcomes (Marks, ; Roemer, ; Nuffer et al, ; Khalil et al, ).…”
Section: Stimulating Intrinsic Motivation In Millennial Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing competency‐based curriculum is not new in medical and allied healthcare professional education programs. In fact, a number of health‐related professions including medicine (Bland et al, ; Jippes et al, ; Mahboob & Evans, ), social work (Nissen, ), nursing (Pijl‐Zieber, Barton, Konkin, Awosoga, & Caine, ), professional psychology (Hatcher et al, ; Kaslow et al, ), athletic training (Peer, ; Schilling & Koetting, ), and dentistry (Chuenjitwongsa, Bullock, & Oliver, ) have documented their experiences with competency‐based education. All professions have documented some of the challenges related to competency‐based education, yet all seem to continue the pursuit of it.…”
Section: Cbe Implementationmentioning
confidence: 99%